Resistivity tomographies to define thickness and water content of pyroclastic covers at Mt. di Vezzi (Ischia Island, Italy) - Di Maio, Rosa; Piegari, Ester; Scotellaro, Cinzia; Soldovieri, Maria Grazia (Italian journal of engineering geology and environment, 2007)
Flowslides are mass movements generally rainfall-induced. These phenomena are very frequent in the Campania Region, whose mountains are diffusively covered with pyroclastic deposits derived from the past volcanic activity. Geophysical techniques may play an important role in investigations of potentially unstable slopes since they provide an accurate knowledge on the in depth distribution of these structures. In this paper, we present and discuss the electrical resistivity tomographies obtained from measurements performed in a landslide area of the Ischia island. This research activity is developed in the frame of a multidisciplinary project by the Earth Science Department of the University of Naples “Federico II” and is motivated by the recent calamitous event of April 2006. It is mainly aimed to define i) the geostructural and physical conditions of the landslide involved area, ii) the guidelines for the monitoring of potential risk areas. The tomographies were performed along two profiles perpendicular each to other and located on the summit portion of Mt. di Vezzi, where the dangerous event of April happened. In order to characterize the shallow structures of the investigated areas, we reached an exploration depth of about 20 m below the ground level. In particular, the high resolution of the electrical tomographic images let us to accurately describe the geometry of pyroclastic deposits overlapping the lava basement. A joint interpretation of geophysical and geological data allowed estimation of the thickness of the pyroclastic covers, and, consequently, the material volumes that could be eventually involved in future flowslide events. Moreover, integration and comparison of our results with other geophysical data coming from laboratory analyses on similar pyroclastic soils allowed an indirect estimation of the water content that, if it is connected to the local slopes, may supply an indication of the stability of the area.